Penggunaan Limbah Domestik Dalam Pembelajaran Keterampilan Meronce Untuk Menumbuhkan Motivasi Kewirausahaan Pada Kelas 5Di SD Muhammadiyah 19 Kemlayan - Ariyanto, Soni Bagus, Drs. Mulyadi SK, S.H., M.Pd (2017)
The background of this study is domestic trash that increase in everyday, so it can pollute the environment. By meronce, the students can process the domestic trash to decrease the pollutant. The aim of this study is to know the use of domestic trash and how to process the domestic trash by meronce to grow the entrepreneurship motivation. The research method is qualitative research by using case study design. The technique of collecting data by using observation, interview, and documentation. While the data validity by using sources triangulation and technique.(1) The result shows that the process of domestic trash in meronce includes : plastic glass, former straw, and plastics.(2) The kind of meronce are : making a drape, making a lampion, making a key hanger, making a bracelet and necklace. The way to grow students' entrepreneurship motivation by selling the masterpiece of meronce at school bazaar and expo that held by school in every year. Then, the benefit of these selling will be saved at class cash.